Examining the Socioeconomic and Health Impacts of Alcohol Consumption among Taxi Drivers - Khatri, Mohan (Karnali Outlook: Knowledge Across Disciplines, 2026)
This study investigated the socioeconomic and health effects of alcohol consumption among taxi drivers in Kathmandu Metropolitan City, Bagmati Province. A survey-based approach was used, and data were gathered through structured interviews. The information was analyzed with descriptive statistics and presented using tables and figures to explore respondents’ socio-demographic details, drinking patterns, and reasons, and health issues related to alcohol use. The results show that regular alcohol use is very common among taxi drivers, with about 65% of Newar, 40% of Brahmin, and 72.5% of Tamang respondents reporting frequent drinking. A smaller number drink occasionally, such as during festivals, celebrations, or monthly. Overall, regular drinking was the most common pattern across all groups. The study also found that Brahmin respondents spent more money on alcohol each month compared to others. These findings have important implications for public health, policy, and socioeconomic stability. The widespread alcohol use among taxi drivers emphasizes the need for targeted awareness campaigns, workplace health programs, and culturally aware prevention strategies. Policies that focus on health education, regulation, and support services are crucial to lowering alcohol-related health risks and reducing its economic and social impacts on drivers and their families.